Asuhan Keperawatan Pada Klien Dengan Stroke Non Hemoragik Di Ruang Stroke Unit Rsd Gunung Jati Kota Cirebon - Putri shintia Devi; Dewi Erna Marisa; Abdul Rouf; Nosa Amelinda Windiani (Awatara Publisher, 2024)
Non-hemorrhagic strokes usually occur due to blockage of brain blood vessels caused by thrombosis, embolism and global hypoperfusion which results in decreased blood supply to brain tissue and leads to ischemia. Therefore, it is necessary to handle it using procedures correctly, namely implementing nursing care including: assessment, nursing diagnosis, planning, implementation and evaluation. The aim of this research is to provide appropriate application of nursing care to clients with non-hemorrhagic stroke in the Stroke Unit. This type of research uses a descriptive method with a case study approach in the form of assessment, data analysis, formulating nursing diagnoses, planning, implementation and evaluation in handling found nursing problems. After providing nursing care to the client Mr. B, the results showed that the nursing problem was partially resolved. The client said his blood pressure had started to decrease, he could move his left leg a little.